Exploring Students' Difficulties in Memorizing English Vocabularies in A Higher Education - Arochman, Taufik; Madani, Syifana Aulia; Welasiyah, Slamet; Setiandari, Rara Kunti (Universitas Pahlawan Tuanku Tambusai, 2023)
Vocabulary is a very important aspect for learners when they are learning a language. More than one million English vocabulary, it is a challenge for them to memorize and know their meaning. In the learning process, many students have difficulty remembering vocabulary. It is this difficulty that makes students experience limited vocabulary when speaking or writing in English. The difficulties experienced by students are of course caused by several factors. This study aims to explore the students’ difficulties in memorizing English vocabularies and the causes. The method used in this study was descriptive qualitative. To collect data and get sample answers, researchers used questionnaire media. In the questionnaire, the researchers presented eight questions with a multiple-choice model. The answers from the respondents were then analysed by researchers and concluded. Based on the findings of the questionnaire, the biggest difficulty experienced by students was being able to understand but not being able to express it with a percentage of 42.9%. The biggest factor that causes students to have difficulty memorizing vocabulary was that they take too long to translate what they want to say with a percentage of 57.1%, followed by their laziness to apply the vocabulary in everyday life with a percentage of 38.1%. The most common solution used by students to overcome difficulties in memorizing vocabulary was that they always want to know the meaning of the vocabulary they read and write it down in notes with a percentage of 71.4%. In this study, the researchers concluded that the most difficulty experienced by students when memorizing vocabulary was that students were able to understand the meaning of their vocabulary but were unable to express it. The most factors that cause difficulties are the time it takes too long to translate what the students want to say and also their laziness. To overcome these difficulties, the most chosen solution is to find out the meaning of new vocabulary and write it on a note